Sasaran Sikap Profesional dalam Profesi Keguruan - Rakhmania Annur Nina; Cantika; Juspita Sari; Takdirmin (STKIP Subang, 2026)
Professional attitude is a fundamental element of the teaching profession that directly affects the quality of learning and the character development of students. This non-empirical article aims to comprehensively examine the targets of teachers’ professional attitudes based on a conceptual literature review of national and international journals published in the last five years (2021–2025). The method employed is a conceptual literature review involving systematic searching, selection, and synthesis of relevant sources. The findings indicate that the targets of professional attitudes include moral and ethical responsibility, commitment to students, continuous professional development, reflective capacity, professional collaboration, and social responsibility in educational contexts. This article emphasizes the importance of systematically integrating professional attitude development into teacher professional courses to ensure that prospective teachers are not only academically competent but also ethically and professionally mature. Keywords: professional attitude, teaching profession, teacher ethics, teacher education